1994
DOI: 10.21273/jashs.119.6.1157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soil Volume on Young Peach Tree Growth and Water Use

Abstract: An experiment designed to study the effects of different root volumes was installed in Fall 1991. `Golden Queen' peach trees [Prunus persica (L.) Batsch.] were planted into different isolated soil volumes (0.025, 0.06, 0.15, 0.4, and 1.0 m3), which were essentially individual drainage lysimeters. Trunk cross-sectional area (TCA) increased from 5.76 to 14.23 cm2 for the smallest and largest volumes, respectively, while leaf area was 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…This first paper (I) addresses the effect on growth and mineral nutrition and a second paper (II) assesses the impact on productivity and wateruse efficiency. The effect of RRV on growth and water use of 1year-old peach trees was reported in a previous paper (Boland et al, 1994).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…This first paper (I) addresses the effect on growth and mineral nutrition and a second paper (II) assesses the impact on productivity and wateruse efficiency. The effect of RRV on growth and water use of 1year-old peach trees was reported in a previous paper (Boland et al, 1994).…”
mentioning
confidence: 68%
“…Individual trees were planted into each compartment, there being 40 trees in each row. The installation of the experiment has been described previously (Boland et al, 1994). In brief, each row consisted of consecutive compartments of different volumes of soil lined with plastic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show a positive relationship between ASV and the number of bunches per vine. By contrast, Boland et al (1994) showed that total flower bud number and flower bud density were inversely related to soil volume for young peach trees. They speculated that this relationship was due to hormonal control or reduced vegetative vigour exhibited by decreased internode length and possibly leading to a greater number of flowers per bud, as found by Williamson et al (1992).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, it is unclear to what extent ASV influences bud fertility in young grapevines and hence potential yield. Increased flower density in response to a reduction in ASV has been observed in both peaches and cherries (Williamson et al 1992, Boland et al 1994, White et al 2001.…”
Section: Introductionmentioning
confidence: 99%